Nonsyndromic Generalized Radiculomegaly of Permanent Dentition: A Rare Case Report - Mohammed Alhussain; Naif Almosa; Hourya Alnofaie (Case Reports in Dentistry)
Introduction. Radiculomegaly (marked elongation of dental roots) is a distinct dental abnormality with a major clinical significance that is closely related to oculofaciocardiodental syndrome (OFCD). Since OFCD syndrome was first identified in 1996, only a few cases of nonsyndromic/nonfamilial radiculomegaly have been reported. We report a new nonsyndromic/nonfamilial radiculomegaly case and the association of OFCD syndrome with the dental challenges. Case Presentation. 18-year-old medically free male presented to the screening dental clinics complaining of teeth malposition. Panoramic radiograph incidentally revealed extremely long and wide roots of almost all dentition. Apical radiographs and cone-beam computed tomography (CBCT) were taken to confirm this anomaly and to rule out any artifact. The images confirmed the excessive length of the roots. A cephalometric X-ray was performed on the patient to rule out any dentofacial deformity. History and physical examinations were negative for ocular or cardiac anomalies. Due to lack of evidence of physical signs and symptoms consistent with OFCD syndrome, genetic testing was not performed. Conclusion. Dentists need to be informed of the clinical and radiographic features of different dental anomalies, especially radiculomegaly, as it is considered one of the significant features of OFCD syndrome. Challenges related to radiculomegaly face dentists while the current literature has not yet provided a solid baseline for managing such patients. The challenges include repairing the root canals, extracting and/or moving the teeth orthodontically. Early diagnosis of the syndrome is crucial to prevent dental challenges and provide the best dental care services.